Solid waste metal-loaded sulfurized carbon nitride photocatalyst as well as preparation method and application thereof

By converting solid waste metal into carbon nitride sulfide photocatalysts supported by solid waste metal, the problems of limited performance of existing photocatalysts and high cost of precious metals are solved, and the performance of photolysis hydrogen production and the use of solid waste are improved.

CN119869587AActive Publication Date: 2025-04-25ANHUI UNIVERSITY OF TECHNOLOGY
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202510063419.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-15
Publication Date
2025-04-25
Estimated Expiration
2045-01-15

AI Technical Summary

Technical Problem

Existing photocatalysts have limited performance in photolysis of hydrogen production, and the cost of precious metals or rare earth metals is high, making it difficult to achieve large-scale production and application.

Method used

By converting solid waste metal into active components of the photocatalyst, a carbon nitride sulfide photocatalyst supported by solid waste metal is prepared, and melamine sulfide is used as a supported precursor, combined with the calcination process of the mixed gas of H2 and Ar to form melamine sulfide carrying S atoms.

Benefits of technology

The carrier concentration of the photocatalyst and the transfer and separation capabilities of the photogenerated electron-hole pair are significantly improved, the catalytic performance of photolysis of hydrogen production is improved, and the high-value utilization of solid waste is realized, reducing costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119869587A_ABST
    Figure CN119869587A_ABST
Patent Text Reader

Abstract

The invention discloses a solid waste metal-loaded sulfurized carbon nitride photocatalyst and a preparation method and application thereof, and the preparation method comprises the following steps: adding electroplating sludge powder into an acid solution to obtain a leachate; melamine is taken and added into the lixivium, and vulcanized melamine containing metal elements is obtained; calcining the vulcanized melamine under the condition of H2 / Ar atmosphere to obtain faint yellow powder; and finally, carrying out ball milling on light yellow powder in a dimethylformamide solution to obtain the solid waste metal atom loaded sulfurized carbon nitride photocatalyst. The metal recovered and extracted from the solid waste is converted into the active component of the photocatalyst, so that the performance of hydrogen production by photolysis of water can be improved, the secondary utilization of the electroplating sludge solid waste resource is realized, the cost is saved, and the preparation process is simple and worthy of popularization and application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of photocatalysts, and in particular to a solid waste metal-loaded carbon sulfide nitride photocatalyst and a preparation method and application thereof. Background Art

[0002] Photocatalysis is an emerging research field that crosses multiple disciplines. Photocatalytic materials are its core because they can realize the conversion of solar energy into chemical energy under mild conditions. Under light conditions, photocatalytic materials produce electrons and holes. Electrons have strong reducing ability and holes have strong oxidizing ability, so redox reactions can occur. Photocatalytic materials have great application value in the production of hydrogen by light decomposition of water, reduction of carbon dioxide, and degradation of organic pollutants. Hydrogen energy is renewable, clean and efficient, and is considered to be an environmentally friendly and sustainable alternative to fossil fuels. In the past few decades, photocatalytic water splitting to produce hydrogen has attracted increasing attention as a new method to produce hydrogen cleanly, at low cost and in an environmentally friendly way using solar energy. In recent years, a new organic polymer semiconductor, graphite carbon nitride, has been considered as a new type of visible light catalyst. Due to its significant advantages, such as simple preparation process, graphite-like sheet structure, consistent conduction band and valence band positions, and stable chemical and physical properties, it has rapidly developed into the research focus of photocatalysts. Among them, metal atoms as active sites of photocatalytic hydrogen production (HER) catalysts are considered to be an important factor in improving HER performance. So far, most of the research on the modification of carbon nitride photocatalysts is mainly based on single precious metal doping, multiple precious metal doping, rare earth metal doping or co-doping of precious metals and rare earth metals. The above precious metal and rare earth metal components used for doping are not only limited in source and difficult to obtain, but also have high costs, making it impossible to mass-produce and apply the photocatalysts prepared from them. Summary of the invention

[0003] In order to solve the above technical problems, the present invention proposes a carbon sulfide nitride photocatalyst loaded with solid waste metals, and a preparation method and application thereof. By converting the metals recovered and extracted from solid waste into active components of the photocatalyst, not only can the photocatalyst achieve improved performance in photocatalytic water splitting to produce hydrogen, but also high-value application of solid waste can be achieved. The extracted and recovered metals replace the use of important metals such as precious metals or rare earth metals, saving costs, and the photocatalyst is worthy of promotion and application.

[0004] In order to achieve the above object, the technical solution adopted by the present invention is:

[0005] In one aspect, the present invention provides a method for preparing a carbon nitride sulfide photocatalyst loaded with solid waste metal, comprising the following steps:

[0006] (1) adding dried electroplating sludge powder into an acid solution, heating and stirring to leach, and obtaining a leachate; adding an appropriate amount of melamine into the leachate, and stirring at room temperature to obtain sulfide melamine containing metal elements;

[0008] (2) the sulfide melamine containing metal elements is heated in H 2 Calcinate in an atmosphere of Ar mixed gas, cool and grind to obtain a light yellow powder;

[0007] (3) placing the light yellow powder in a dimethylformamide solution and continuing to ball-mill, filtering, washing, and drying to obtain a carbon nitride sulfide photocatalyst loaded with solid waste metal.

[0008] Preferably, in step (1), the particle size of the electroplating sludge powder is 200-300 meshes.

[0009] Preferably, in step (1), the metal content of the electroplating sludge powder is 20-30wt%, and the metal elements include one or two of Fe and Al.

[0010] Preferably, in step (1), the acid solution is one or a mixture of nitric acid solution, dilute sulfuric acid solution, and hydrochloric acid solution, and the concentration of the acid solution is 3 to 6 mol / L.

[0011] Preferably, in step (1), the leaching temperature is 50-70° C., and the leaching time is 5-8 hours.

[0012] Preferably, in step (1), the dosage ratio of the melamine to the leaching solution is 0.8-1.5 mg: 15-20 μL.

[0013] Preferably, in step (2), the H 2 H in mixed gas with Ar 2 The ratio of Ar is 5% to 20%.

[0014] Preferably, in step (2), the calcination temperature is 450-500° C. and the calcination time is 3-5 h.

[0015] Another aspect of the present invention provides a solid waste metal-loaded sulfidized carbon nitride photocatalyst, which is prepared by the above-mentioned preparation method of the solid waste metal-loaded sulfidized carbon nitride photocatalyst.

[0016] Another aspect of the present invention provides an application of a sulfidized carbon nitride photocatalyst loaded with solid waste metals, wherein the sulfidized carbon nitride photocatalyst is applied to a photocatalytic water decomposition hydrogen production reaction under neutral conditions.

[0017] Compared with the prior art, the present invention has the following beneficial effects:

[0018] Solid wastes such as electroplating sludge generated in the steel production process contain a variety of metal elements and inorganic compounds. These electroplating sludges must be specially treated before they can be discharged, otherwise they will cause great heavy metal pollution to the environment. The present invention uses an acid leaching method to extract metal elements from the electroplating sludge, and at the same time uses sulfur in the leachate to sulfidize melamine to form sulfide melamine, and then uses a stirring adsorption method to dope the metal elements into the sulfide melamine to form sulfide melamine containing metal elements, and then calcines it and places it in a dimethylformamide solution for grinding, and finally obtains a sulfide nitride carbon photocatalyst loaded with solid waste metal elements. The preparation process is simple, easy to operate and easy to prepare on a large scale, not only realizing the secondary utilization of electroplating sludge solid waste, but also using recycled iron and aluminum to replace the use of important metals such as precious metals or rare earth metals, saving costs, and worthy of popularization and application.

[0019] The solid waste metal-doped sulfided carbon nitride photocatalyst synthesized by the present invention is different from the existing ordinary melamine. The present technical solution uses the sulfur in the solid waste sludge leachate to sulfidize the melamine to form sulfided melamine carrying S atoms, and uses sulfided melamine as a loading precursor. Due to the introduction of S atoms and metal elements, the carrier concentration of the photocatalyst is significantly increased, and the transfer, separation, oxidation and reduction capabilities of photogenerated electron-hole pairs are improved, thereby greatly improving its catalytic performance of photolysis of water to produce hydrogen. In addition, due to the introduction of S atoms and metal elements, the photocatalyst shows high absorption performance in the ultraviolet light region and the visible light region, making its light capture ability more sensitive, more active, and more catalytic efficiency.

[0020] The solid waste metal-doped carbon sulfide nitride photocatalyst synthesized by the present invention has a good photocatalytic performance under different ratios of H 2 When calcined in a mixed gas of Ar, the metal-doped carbon sulfide nitride will gradually delaminate and peel off as the proportion of hydrogen increases. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 XRD diagrams of the solid waste metal-loaded sulfidized carbon nitride photocatalysts prepared in Example 1, Example 2, and Example 3 and the catalyst prepared in Comparative Example 1;

[0023] Figure 2 Transmission electron microscope images of the solid waste metal-loaded carbon nitride sulfide photocatalysts prepared in Examples 1, 2, and 3 and the catalyst prepared in Comparative Example 1 (a is Comparative Example 1; b is Example 1; c is Example 2; d is Example 3);

[0024] Figure 3The performance diagram of the solid waste metal loaded sulfide nitride carbon photocatalyst prepared in Example 1, Example 2, Example 3 and the catalyst obtained in Comparative Example 1 in HER.

[0025] Figure 4 The recyclability of the solid waste metal loaded sulfide nitride carbon photocatalyst prepared in Example 2 in the photocatalytic hydrogen evolution cycle under visible light.

[0026] Figure 5 The electron paramagnetic resonance (EPR) images of the sulfidized carbon nitride photocatalyst loaded with solid waste metal (S-CN) prepared in Example 2 and the comparative example 1 (CN).

[0027] Figure 6 The UV-visible diffuse reflectance spectra (DRS) of the sulfidized carbon nitride photocatalyst loaded with solid waste metal (S-CN) prepared in Example 2 and the comparative example 1 (CN).

[0028] Figure 7 Fourier transform infrared (FTIR) spectra of the sulfidized carbon nitride photocatalyst loaded with solid waste metal (S-CN) prepared in Example 2 and Comparative Example 1 (CN). DETAILED DESCRIPTION

[0029] The specific embodiments of the present invention are further described below. It should be noted that the description of these embodiments is used to help understand the present invention, but does not constitute a limitation of the present invention. In addition, the technical features involved in each embodiment of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0030] The experimental methods in the following examples are conventional methods unless otherwise specified, and the experimental materials used in the following examples can be purchased through conventional commercial channels unless otherwise specified. In some specific embodiments of the present invention, the electroplating sludge powder is electroplating sludge generated in the steel production process, and its main components after drying include the following components by mass fraction: The rest are inevitable impurities.

[0031] The embodiment of the present invention provides a method for preparing a carbon nitride sulfide photocatalyst loaded with solid waste metal, and the specific overall process is as follows:

[0032] (1) Dry and crush the electroplating sludge solid waste into powder, weigh 100g of the electroplating sludge powder sieved to 200-300 mesh, add it to the prepared 3-6 mol / L acid solution, stir it in a water bath at 50-70°C for 5-8h, and then filter it to obtain a leachate; take 1-2g of melamine and add it to 20-40ml of the leachate, stir it at room temperature for 7-10h to obtain sulfide melamine containing metal elements. In some specific embodiments of the present invention, the acid solution is a mixture of one or more of nitric acid solution, dilute sulfuric acid solution, and hydrochloric acid solution; the metal element includes one or two of Fe and Al.

[0033] (2) the sulfide melamine containing metal elements is mixed with H 2 The mixture is placed in a tube furnace and calcined under an atmosphere of Ar mixed gas, cooled and ground to obtain a light yellow powder. 2 H in mixed gas with Ar 2 The ratio of Ar / Ar is 5% to 20%, the calcination temperature is 500°C, and the calcination time is 3 hours. The elements in the light yellow powder are detected by ICP (inductively coupled plasma atomic emission spectrometer) and the results show that the S content is 0.59wt%, the Al content is 0.12wt%, the Fe content is 0.73wt%, and the rest are other elements or metal elements, such as Ca.

[0032] (3) adding the light yellow powder obtained in step (2) to a dimethylformamide (DMF) solution and milling the powder in a planetary ball mill, wherein the ball-to-material ratio is 1:200 and the rotation speed is 300-400 rpm. After milling for 2-3 hours, the powder is dried to obtain a carbon sulfide nitride photocatalyst loaded with solid waste metal, i.e., a photocatalyst. The embodiment of the present invention also provides an application of a sulfidized carbon nitride photocatalyst prepared by the above-mentioned preparation method of the sulfidized carbon nitride photocatalyst loaded with solid waste metal, which is specifically applied to the photocatalytic decomposition of water to produce hydrogen under neutral conditions.

[0033] The present invention will be further described below with reference to specific embodiments, but is not limited thereto.

[0034] Example 1

[0035] This embodiment provides a method for preparing a carbon nitride sulfide photocatalyst loaded with solid waste metal, which specifically comprises the following steps:

[0036] (1) drying and crushing the electroplating sludge solid waste into powder, weighing 100 g of the electroplating sludge powder sieved to 200 mesh, adding it to the prepared 3 mol / L nitric acid solution, stirring it in a water bath at 60° C. for 5 h, and then filtering it to obtain a leaching solution; taking 1 g of melamine and adding it to 20 ml of the leaching solution, stirring it at room temperature for 8 h to obtain sulfide melamine containing Fe and Al metal elements;

[0037] (2) The sulfide melamine containing Fe and Al metal elements is mixed in 5% H 2 Under the condition of mixed gas atmosphere of Ar / Ar, the mixture was calcined in a tube furnace at 500℃ for 3h, cooled and ground to obtain a light yellow powder;

[0038] (3) The light yellow powder obtained in step (2) was added to the DMF solution and ball-milled in a planetary ball mill at a rotation speed of 300 rpm. After ball-milling for 3 h, the solid waste metal-loaded carbon sulfide nitride photocatalyst was obtained by drying, which was recorded as photocatalyst 1.

[0039] Example 2

[0040] This embodiment provides a method for preparing a carbon nitride sulfide photocatalyst loaded with solid waste metal, which specifically comprises the following steps:

[0041] (1) drying and crushing the electroplating sludge solid waste into powder, weighing 100 g of the solid waste powder sieved to 250 mesh, adding it to a prepared 5 mol / L nitric acid solution, stirring it in a water bath at 60° C. for 6.5 hours, and then filtering it to obtain a leachate; taking 1 g of melamine, adding it to 20 mL of the leachate, and stirring it at room temperature for 8 hours to obtain sulfide melamine containing Fe and Al metal elements;

[0042] (2) The sulfide melamine containing Fe and Al metal elements is mixed in 10% H 2 Under the condition of mixed gas atmosphere of Ar / Ar, the mixture was calcined in a tube furnace at 500℃ for 3h, cooled and ground to obtain a light yellow powder;

[0043] (3) The light yellow powder obtained in step (2) was added to the DMF solution and ball-milled in a planetary ball mill at a rotation speed of 300 rpm. After ball-milling for 3 h, the solid waste metal-loaded carbon sulfide nitride photocatalyst was obtained by drying, which was recorded as photocatalyst 2.

[0044] Example 3

[0045] This embodiment provides a method for preparing a carbon nitride sulfide photocatalyst loaded with solid waste metal, which specifically comprises the following steps:

[0046] (1) drying and crushing the electroplating sludge solid waste into powder, weighing 100 g of the electroplating sludge powder sieved to 300 mesh, adding the prepared 6 mol / L nitric acid solution, stirring in a water bath at 60° C. for 8 h, and then filtering to obtain a leachate; taking 1 g of melamine, adding it to 20 mL of the leachate and stirring at room temperature for 8 hours to obtain sulfide melamine containing Fe and Al metal elements;

[0047] (2) The sulfide melamine containing Fe and Al metal elements is heated in 20% H 2 Under the condition of mixed gas atmosphere of Ar / Ar, the mixture was calcined in a tube furnace at 500℃ for 3h, cooled and ground to obtain a light yellow powder;

[0048] (3) The light yellow powder obtained in step (2) was added to the DMF solution and ball-milled in a planetary ball mill at a rotation speed of 300 rpm. After ball-milling for 3 h, the powder was dried to obtain a carbon sulfide nitride photocatalyst loaded with solid waste metal, which was recorded as photocatalyst 3.

[0049] Comparative Example 1

[0050] This comparative example provides a method for preparing a carbon nitride photocatalyst for hydrogen production by water splitting. The main difference between the method and Example 1 is that no electroplating sludge solid waste is added. The method specifically comprises the following steps:

[0051] (1) 1 g of melamine was placed in a crucible, and then transferred to a box furnace and calcined at 500 °C for 3 h to obtain carbon nitride;

[0052] (2) 100 mg of the carbon nitride obtained in step (1) was added to the DMF solution and ball-milled in a planetary ball mill at a speed of 300 rpm for 3 h. The powder was dried and recorded as catalyst 4.

[0053] The catalyst obtained above was subjected to performance testing, and the specific testing process is as follows:

[0054] (1) Weighing 10 mg of the catalyst powders obtained in Example 1, Example 2 and Example 3 respectively, adding 0.2 mg of platinic acid, 16 mL of deionized water and 4 mL of methanol sacrificial agent to each catalyst powder, and ultrasonicating at room temperature for 1 hour to obtain a uniformly dispersed catalyst suspension;

[0055] (2) Weigh 10 mg of the catalyst powder obtained in Comparative Example 1, add 0.2 mg of platinic acid, 16 ml of deionized water and 4 mL of methanol sacrificial agent, respectively, and perform ultrasonic treatment at room temperature for 1 hour to obtain a uniformly dispersed catalyst suspension;

[0056] (3) In the HER performance test, the suspensions obtained in step (1) and step (2) were subjected to comparative tests. The specific experimental method was as follows: first, the suspension was poured into a highly transparent quartz reactor, and then purged with nitrogen and vacuumed to remove impurity gases, and the process was repeated three times. The reactor was irradiated with a 300W xenon lamp to simulate sunlight for 4 hours to realize the photocatalytic water splitting hydrogen production reaction system;

[0057] (4) Extract the gas generated in the reactor in step (3) every hour, and then use the TCD detector in the gas chromatograph to perform qualitative and quantitative analysis on the collected gas, such as Figure 3 It can be seen that the HRE catalyst prepared in Example 2 has better performance than that prepared in Example 1 and Example 3, and the performance of the catalysts obtained in Examples 1-3 is significantly higher than that of the catalyst 4 obtained in Comparative Example 1, wherein the hydrogen production yield of the catalyst 2 in Example 2 is 27.34 mmol·g -1 ·h -1 The hydrogen production rate of catalyst 1 in Example 1 was 18.38 mmol·g -1 ·h -1 The hydrogen production rate of catalyst 3 in Example 3 was 16.26 mmol·g -1 ·h -1 , while the hydrogen production yield of catalyst 4 in comparative example 1 was 3.23 mmol·g -1 ·h -1 The performance of HRE catalyst 2 prepared in Example 2 is much higher than that of catalyst 4 prepared in Comparative Example 1, and its hydrogen yield is 8.5 times higher than that of Comparative Example 1, indicating that the sulfided carbon nitride photocatalyst prepared by sulfided melamine loaded with solid waste metal can significantly improve the performance of photocatalytic water splitting to produce hydrogen.

[0058] Conclusion analysis of the catalyst:

[0059] (1) Figure 2 The morphological characteristics of the photocatalysts obtained in various embodiments and comparative examples of the present invention are shown. Figure 2 (b)(c)(d) It can be seen that as the hydrogen ratio of each photocatalyst in the examples increases, the metal-doped carbon sulfide nitride photocatalyst gradually delaminates and peels off.

[0060] (2) Figure 5 The electron paramagnetic resonance (EPR) images of the sulfidized carbon nitride photocatalyst loaded with solid waste metal (S-CN) prepared in Example 2 and Comparative Example 1 (CN) are shown in FIG. It can be seen from the figure that the photocatalyst of Example 2 forms defect oxygen vacancies with the introduction of S atoms and metal elements, which significantly increases the carrier concentration and improves the transfer, separation, oxidation and reduction capabilities of photogenerated electron-hole pairs.

[0061] (3) Figure 6The UV-visible diffuse reflectance spectra (DRS) of the sulfidized carbon nitride photocatalyst (S-CN) loaded with solid waste metal prepared in Example 2 and Comparative Example 1 (CN). It can be seen from the figure that the photocatalyst S-CN shows high absorption performance in the ultraviolet light region less than 400nm, and shows good absorption performance for ultraviolet light. For the visible light region greater than 400nm, due to the introduction of S atoms and metal elements, the absorption band intensity of the photocatalyst S-CN increases, and the visible light absorption area is larger than that of the catalyst CN in Comparative Example 1, indicating that the absorption performance of the photocatalyst S-CN for visible light is stronger than that of the catalyst CN, that is, the photocatalyst S-CN is more sensitive to light capture, making its catalytic efficiency better.

[0062] (4) Figure 7 The Fourier transform infrared (FTIR) spectra of the sulfidized carbon nitride photocatalyst loaded with solid waste metal (S-CN) prepared in Example 2 and the comparative example 1 (CN). The S-CN and CN structures have a wavelength of 1100-1600 cm -1 Typical vibration peaks of triazine heterocyclic structure can be observed, including: 1613cm -1 CN bond stretching vibrations at 1250, 1333 and 1365 cm -1 Aromatic CN bond stretching vibration at 1615 cm -1 SCN bond stretching vibrations at 1262, 1322 and 1362 cm -1 In addition, at 810 cm -1 A significant triazine bending vibration peak can be observed at 3000-3700 cm -1 The stretching vibration peak of NH can be observed. The above infrared analysis results show that both substances contain triazine rings composed of extended C=N. Moreover, the infrared absorption peak of S-CN is significantly narrower than that of ordinary CN, indicating that it has better crystallization performance, a wider range of delocalized π bonds in its structure, better mobile phase of electrons, and stronger oxidation and reduction capabilities.

[0063] The embodiments of the present invention are described in detail above, but the present invention is not limited to the described embodiments. For those skilled in the art, various changes, modifications, substitutions and variations of these embodiments are made without departing from the principles and spirit of the present invention, and still fall within the protection scope of the present invention.

Claims

1. A method for preparing a carbon nitride sulfide photocatalyst loaded with solid waste metal, characterized in that: The following steps are involved: (1) adding dried electroplating sludge powder into an acid solution, heating and stirring to leach, and obtaining a leachate; adding an appropriate amount of melamine into the leachate, and stirring at room temperature to obtain sulfide melamine containing metal elements; (2) calcining the melamine sulfide containing metal elements in an atmosphere of a mixed gas of H2 and Ar, cooling, and grinding to obtain a light yellow powder; (3) placing the light yellow powder in a dimethylformamide solution and continuing to ball-mill, filtering, washing, and drying to obtain a carbon nitride sulfide photocatalyst loaded with solid waste metal.

2. The method for preparing the solid waste metal-loaded carbon nitride sulfide photocatalyst according to claim 1, characterized in that: In the step (1), the particle size of the electroplating sludge powder is 200 to 300 meshes.

3. The method for preparing the solid waste metal-loaded carbon nitride sulfide photocatalyst according to claim 1, characterized in that: In the step (1), the metal element content of the electroplating sludge powder is 20-30wt%, and the metal element includes one or two of Fe and Al.

4. The method for preparing the solid waste metal-loaded carbon nitride sulfide photocatalyst according to claim 1, characterized in that: In the step (1), the acid solution is one or a mixture of nitric acid solution, dilute sulfuric acid solution, and hydrochloric acid solution, and the concentration of the acid solution is 3 to 6 mol / L.

5. The method for preparing the solid waste metal-loaded carbon nitride sulfide photocatalyst according to claim 1, characterized in that: In the step (1), the leaching temperature is 50-70° C., and the leaching time is 5-8 hours.

6. The method for preparing the solid waste metal-loaded carbon nitride sulfide photocatalyst according to claim 1, characterized in that: In the step (1), the dosage ratio of the melamine to the leaching solution is 0.8-1.5 mg: 15-20 μL.

7. The method for preparing the solid waste metal-loaded carbon nitride sulfide photocatalyst according to claim 1, characterized in that: In the step (2), the ratio of H2 / Ar in the H2 and Ar mixed gas is 5% to 20%.

8. The method for preparing the solid waste metal-loaded carbon nitride sulfide photocatalyst according to claim 1, characterized in that: In the step (2), the calcination temperature is 450-500° C. and the calcination time is 3-5 hours.

9. A sulfidized carbon nitride photocatalyst loaded with solid waste metal, characterized in that: The photocatalyst is prepared by the method for preparing the sulfidized carbon nitride photocatalyst loaded with solid waste metal according to any one of claims 1 to 8.

10. An application of the solid waste metal-loaded carbon nitride sulfide photocatalyst as claimed in claim 9, characterized in that: The sulfide carbon nitride photocatalyst is used for photocatalytic decomposition of water to produce hydrogen under neutral conditions.

Citation Information

Patent Citations

  • Carbon nitride photocatalytic material and preparation method thereof

    CN110280289A

  • Hollow annular carbon nitride photocatalyst and preparation method thereof

    CN112675894A

  • Red mud modified carbon nitride nano material as well as preparation method and application thereof

    CN113877621A

  • Double-vacancy graphite phase carbon nitride photocatalyst and preparation method thereof

    CN113908872A

  • Recycling method of copper-containing electroplating sludge, prepared copper-doped carbon nitride material and application

    CN115779945A